2016
DOI: 10.1007/s10461-016-1641-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder Symptoms Among People Living with HIV/AIDS in Rural China

Abstract: Among people living with HIV/AIDS (PLHA), the occurrence of post-traumatic stress disorder (PTSD) symptoms associated with HIV diagnosis is a common problem. This study examined HIV diagnosis-related PTSD symptoms and its associated factors among PLHA in rural China. We used baseline data from a randomized controlled trial conducted in Anhui Province, China. Surveys of 522 PLHA were conducted via computer-assisted personal interview method. PTSD symptoms were measured based on re-experiencing, avoidance and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…PLWH who experienced high PTSD symptoms following their diagnosis, treatment, and disease progression were more likely to experience poor HRQoL. This finding agrees with Luo et al (2017), Nightingale et al (2011), andPence et al (2012) who reported similar findings across samples of PLWH. Therefore, the more the PLWH experienced negative mental health aftermath of trauma, the more their HRQoL worsens.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…PLWH who experienced high PTSD symptoms following their diagnosis, treatment, and disease progression were more likely to experience poor HRQoL. This finding agrees with Luo et al (2017), Nightingale et al (2011), andPence et al (2012) who reported similar findings across samples of PLWH. Therefore, the more the PLWH experienced negative mental health aftermath of trauma, the more their HRQoL worsens.…”
Section: Discussionsupporting
confidence: 86%
“…Studies (example, Cohen et al, 2009; Haagsma et al, 2012; Luo et al, 2017; Nadim et al, 2012; Nightingale et al, 2011; Pence et al, 2012; Wintermann et al, 2019) have consistently found PTSD symptoms to be negatively associated with poor HRQoL among patients living with various chronic and trauma-inducing health conditions, including PLWH. However, little is known about the process by which PTSD symptoms are associated with poor HRQoL.…”
mentioning
confidence: 99%
“…Incongruously, living with HIV was associated with lower odds of having PTSS. HIV and COVID-19 intersectional studies had indicated the increased risk of PTSD for PLHIV who have experienced traumatic events like intimate partner violence, isolation, discrimination, stigma, and challenges with obtaining treatment [76]. Although we did not explore the history of traumatic events for respondents living with HIV in this study, past studies have indicated that PLHIV are at high risk of facing these traumatic events [77,78].…”
Section: Discussionmentioning
confidence: 91%
“…In addition, being diagnosed with HIV, a life-threatening illness, is a potentially traumatic event in and of itself, and PTSD may emerge as a result of this diagnosis. Infection with HIV causes a progressive destruction of the immune system, which increases the susceptibility to malignancies that threaten a person’s life, and being labelled and associated with HIV stigma, taking multiple daily medications and experiencing repeated unpleasant side effects constitute potentially traumatic events 10. These high rates of potential trauma exposure during the course of the illness may also increase the likelihood of developing PTSD.…”
Section: Introductionmentioning
confidence: 99%